2022
DOI: 10.1094/pdis-10-21-2186-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium Wilt of Industrial Hemp (Cannabis sativa) Caused by Fusarium oxysporum in Northeast China

Abstract: Industrial hemp (Cannabis sativa L.) is an ancient and economically important crop used in food, medicine, textile, and paper industries (Chandra et al. 2017). In July 2021, an estimated 30% of the industrial hemp plants showed wilted leaves and root rot in the greenhouse at the Modern Agriculture Demonstration Area Management Center, Harbin City, Heilongjiang Province, China. Initially, the diseased plants exhibited green and reversible wilting of lower canopy leaves. Upon progression the plants showed irreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…An early study showed that certain species of the fungi genus Fusarium were pathogenic and could cause fusarium wilt disease in watermelon monoculture [61]. Fusarium oxysporum was also isolated from rhizosphere soils of industrial hemp where fusarium wilt occurred [16]. Therefore, we hypothesize that the increased disease incidence in industrial hemp after monoculture cropping was mainly due to the abundance of Fusarium oxysporum.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…An early study showed that certain species of the fungi genus Fusarium were pathogenic and could cause fusarium wilt disease in watermelon monoculture [61]. Fusarium oxysporum was also isolated from rhizosphere soils of industrial hemp where fusarium wilt occurred [16]. Therefore, we hypothesize that the increased disease incidence in industrial hemp after monoculture cropping was mainly due to the abundance of Fusarium oxysporum.…”
Section: Discussionmentioning
confidence: 88%
“…However, previous studies showed that continuous cropping in greenhouse results in crop yield decline, poor quality, and increased occurrence of diseases and insect pests [13][14][15]. Our previous study found that fusarium wilt occurred in industrial hemp after continuous cropping, and the pathogen Fusarium oxysporum was identified [16]. The pathogen Fusarium oxysporum could lead to monoculture watermelon decreases in crop yield and quality [17].…”
Section: Introductionmentioning
confidence: 99%